2011
DOI: 10.1002/mop.25982
|View full text |Cite
|
Sign up to set email alerts
|

Broadband bluetooth antenna based on Co2Z hexaferrite‐glass composite

Abstract: Bluetooth ferrite antenna was fabricated on Co2Z (Ba3Co2Fe24O41) hexaferrite‐glass composite substrate and characterized. The fabricated antenna has a total volume of 36 mm3 (3 × 8 × 1.5 mm3) and showed wide bandwidth (390 MHz at VSWR < 2). The maximum 3D peak‐gain and radiation efficiency were measured to be 3.32 dBi at 2.35 GHz and 77.7% at 2.3 GHz, respectively. The 3D peak gain of 2.45 dBi and 3D average gain of −1.89 dBi were obtained at the Bluetooth central frequency of 2.45 GHz. © 2011 Wiley Periodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…Composites with magnetic and dielectric properties are versatile and thus employed in microwave and RF applications, such as antennas and electromagnetic wave absorbers . These composites are typically polymer‐ or ceramic‐based soft ferrite composites .…”
Section: Introductionsupporting
confidence: 75%
“…Composites with magnetic and dielectric properties are versatile and thus employed in microwave and RF applications, such as antennas and electromagnetic wave absorbers . These composites are typically polymer‐ or ceramic‐based soft ferrite composites .…”
Section: Introductionsupporting
confidence: 75%
“…Very recently, some solutions in millimeter waves began to be considered and the MMID (Millimeter wave IDentification) acronym is introduced in the literature [4]. Then, the trend is an increase in frequency for new applications whose scope is still very open and also for actual green topics [5]. If RFID denomination evolves, its two main characteristics, the wireless and powerless are decisive advantages on emerging wireless technologies.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, hexaferrite material was used in our MIMO antenna design as ferrite has miniaturization capability due to its permeability and permittivity [5,6]. This is because effective wavelength, k eff ¼ k 0 = ffiffiffiffiffiffiffiffi l r e r p , can be reduced due to both permeability (l r ) and permittivity (e r ), where k 0 is the freespace wavelength.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some investigations have indicated that microwave absorbing materials employing CIP as an absorbent showed promising microwave absorbing properties due to its high permeability and Snoek's limit. Low melting point glass (LMPG) has been used as a matrix and high temperature adhesive bonding to prepare many composites, such as glass/BaTiO 3 [23,24], glass/ZnAl 2 O 4 [25] and glass/Co 2 Z ferrite [26,27], because of its capability of melting at a relatively low temperature. The aim of this work is to prepare the 40 vol% carbonyl iron/glass composite absorber using LMPG as the matrix and CIP as the filler.…”
Section: Introductionmentioning
confidence: 99%